Adaptation and Validation of the Cyberbullying Scale in Indonesian Version: Exploratory and Confirmatory Factor Analysis Approach - Winda Laura Martcelina; Untung Dimas Prayogi; Ghifari Azhar Fadiyah; Apriliani Fitriana; Shri Latifani; Muhammad Rakha Nugraha; Devi Wulandari; Christiany Suwartono (Sinergi International Journal of Psychology, 2026)
Cyberbullying has become a major psychosocial issue among adolescents alongside the rapid growth of digital media use. This study aimed to adapt and evaluate the validity and reliability of the Indonesian version of the Cyberbullying Scale (CBS) developed by Stewart et al. (2014). A descriptive quantitative design was used involving 392 adolescents aged 12–18 years from 10 provinces in Indonesia, recruited through purposive sampling via an online survey. The adaptation followed WHO cross-cultural adaptation guidelines, including forward translation, backward translation, expert review, and pilot testing. Data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) with JASP software. EFA results showed a unidimensional structure with an eigenvalue of 9.628 explaining 68.8% of the total variance, while all items demonstrated strong factor loadings (0.689–0.889) without item removal. CFA confirmed significant item loadings on the cyberbullying factor (0.643–0.976, p < 0.001). Reliability analysis indicated excellent internal consistency (α = 0.968). However, CFA global fit indices were below recommended thresholds (CFI = 0.839, TLI = 0.809, RMSEA = 0.182), suggesting that the one-factor model may not fully represent cyberbullying experiences in the Indonesian context. Overall, the Indonesian CBS showed strong reliability and item-level validity, although further refinement and cross-validation are needed before broader application among Indonesian adolescentsCyberbullying has become a major psychosocial issue among adolescents alongside the rapid growth of digital media use. This study aimed to adapt and evaluate the validity and reliability of the Indonesian version of the Cyberbullying Scale (CBS) developed by Stewart et al. (2014). A descriptive quantitative design was used involving 392 adolescents aged 12–18 years from 10 provinces in Indonesia, recruited through purposive sampling via an online survey. The adaptation followed WHO cross-cultural adaptation guidelines, including forward translation, backward translation, expert review, and pilot testing. Data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) with JASP software.EFA results showed a unidimensional structure with an eigenvalue of 9.628 explaining 68.8% of the total variance, while all items demonstrated strong factor loadings (0.689–0.889) without item removal. CFA confirmed significant item loadings on the cyberbullying factor (0.643–0.976, p < 0.001). Reliability analysis indicated excellent internal consistency (α = 0.968). However, CFA global fit indices were below recommended thresholds (CFI = 0.839, TLI = 0.809, RMSEA = 0.182), suggesting that the one-factor model may not fully represent cyberbullying experiences in the Indonesian context. Overall, the Indonesian CBS showed strong reliability and item-level validity, although further refinement and cross-validation are needed before broader application among Indonesian adolescents.